Hedonic price for amenities in rural and urban residential condominiums in Costa Rica - Paniagua Molina, Hernán Javier (2021)
As the number of homes located in condominiums increases, investigations should be promoted to determine the implied price of additional amenities over the total price of the property. This study evaluated the impact of multi-attribute and construction variables on the value of condominiums in Costa Rica, using a hedonic pricing model of the amenities that influence the total price. Information from condominiums located in all provinces of the country was used to determine the importance of the variables studied. Through multiple regression analysis, it was determined that nine amenities explain the behavior of the total price. This study shows that the project's internal and external variables have a significant effect on sales prices and consumers' purchasing decisions. The most significant variables were income, construction area, access to a pool and gym, and the type of condominium.